고온 및 저온에서 육묘된 파프리카 묘의 소질과 정식 후 초기 생육 반응 - 조윤희(Yun-Hee Cho); 김치선(Chi-Seon Kim); 김정만(Jeong-Man Kim); 구양규(Yang Gyu Ku); 김호철(Ho Cheol Kim) (Weon'ye gwahag gi'sulji, 2016)
The effect of high and low temperatures on seedling quality while raising of paprika (Capsicum annuum L.) seedlings, and their early development after planting was investigated. The control raising seedling temperature (RST) was $23^{°}C$; high temperature, $31^{°}C$; and low temperature, $15^{°}C$ throughout the raising seedling period. At $15^{°}C$ and $30^{°}C$, plant height, stem diameter, fresh weight, dry weight, number of leaves, and seedling leaf area were significantly lower than those at $23^{°}C$. At 4 weeks after planting, seedling's growth characteristics showed a similar pattern. Compared to $23^{°}C$, seedlings raised at $15^{°}C$ and $30^{°}C$ had an increased dry weight and leaf area per unit time after planting than during the seedling raising period. At 4 weeks after planting, crop growth rate and leaf area index were unaffected by RST, and relative growth rate and net assimilation rate at RSTs of $15^{°}C$ and $31^{°}C$ were higher than those those at RST of $23^{°}C$. At an RST of $15^{°}C$, growth speed and net assimilation rates were higher after planting than before planting, according to increased photosynthetic rate. Thus, high and low temperatures during the seedling raising period significantly reduced seedling growth and plant growth after planting. After planting, seedlings raised at $15^{°}C$ recovered more quickly than did those raised at $31^{°}C$. 본 연구에서는 고온 및 저온의 육묘 온도가 파프리카 묘의 소질 및 정식 후 초기 생육에 미치는 영향을 알아보았다. 육묘 온도는 다용되고 있는 $23^{°}C$를 대조구로 하여 고온을 $31^{°}C$, 저온을 $15^{°}C$로 처리하였다. 육묘 온도에 따라 자란 묘의 초장, 줄기직경, 생체중, 건물중, 엽수, 엽면적 등은 $15^{°}C$와 $31^{°}C$ 처리구에서 대조구보다 유의하게 낮았다. 그리고 그 묘들의 정식 4주 후 식물체 특성에서도 같은 경향을 나타내었다. 대조구 대비 $15^{°}C$와 $31^{°}C$ 처리구의 단위 시간 당 건물중 및 엽면적의 증가 속도는 육묘 기간보다 정식 후에 크게 높아졌다. 정식 후 4주 간 자란 $15^{°}C$와 $31^{°}C$ 처리구의 식물체의 작물생장속도와 엽면적지수는 대조구와 유의한 차이를 나타내지 않았고, 상대생장율과 순동화율은 유의하게 높았다. 이러한 $15^{°}C$처리구의 정식 후 생장 속도 및 순동화율의 증가는 정식 후 정식 전에 비해 크게 높아진 광합성 능력에서 기인하였다. 이상의 결과를 요약하면, 파프리카의 저온 및 고온 육묘온도는 묘 및 정식 후 식물체의 생육을 저하시켰다. 그리고 정식 후의 식물체의 회복 속도는 $31^{°}C$보다 $15^{°}C$에서 육묘된 묘에서 빨랐다.